Designing supply networks under maximum customer order lead times. Issue 10 (2nd October 2016) - Meisel, Frank; Rei, Walter; Gendreau, Michel; Bierwirth, Christian
ABSTRACT: We consider the problem of designing supply networks for producing and distributing goods under restricted customer order lead times. Companies apply various instruments for fulfilling orders within preset lead times, such as locating facilities close to markets, producing products to stock, choosing fast modes of transportation, or delivering products directly from plants to customers without the use of distribution centers. We provide two alternative models that consider these options to a different extent, when designing multi-layer, multi-product facility networks that guarantee meeting restricted lead times. A computational evaluation compares both models with respect to solvability and the quality of the obtained networks. We find that formulating the problem as a time–space network flow model considerably helps to design high-quality networks. Furthermore, the lead times quoted to customers affect the design of all layers in the supply network. In turn, this shows that when service requirements are applied, the strategic planning of the network should be adapted accordingly. Concerning the instruments considered for meeting quoted lead times, the choice between make-to-order and make-to-stock production is found to be of utmost importance, whereas transportation decisions have a minor impact.